Control of the Unfolded Protein Response in Health and Disease. (August 2017) - Doultsinos, Dimitrios; Avril, Tony; Lhomond, Stéphanie; Dejeans, Nicolas; Guédat, Philippe; Chevet, Eric
The unfolded protein response (UPR) is an integrated, adaptive biochemical process that is inextricably linked with cell homeostasis and paramount to maintenance of normal physiological function. Prolonged accumulation of improperly folded proteins in the endoplasmic reticulum (ER) leads to stress. This is the driving stimulus behind the UPR. As such, prolonged ER stress can push the UPR past beneficial functions such as reduced protein production and increased folding and clearance to apoptotic signaling. The UPR is thus contributory to the commencement, maintenance, and exacerbation of a multitude of disease states, making it an attractive global target to tackle conditions sorely in need of novel therapeutic intervention. The accumulation of information of screening tools, readily available therapies, and potential pathways to drug development is the cornerstone of informed clinical research and clinical trial design. Here, we review the UPR's involvement in health and disease and, beyond providing an in-depth description of the molecules found to target the three UPR arms, we compile all the tools available to screen for and develop novel therapeutic agents that modulate the UPR with the scope of future disease intervention.